Composite surfaces after finishing and polishing techniques - Turssi, C. P.; Saad, JRC; Duarte, SLL; Rodrigues, A. L. (Mosher & Linder, Inc, 2000)
Purpose: To evaluate the effect of finishing and polishing techniques on surface roughness of resin-based composites (RBCs). Materials and Methods: Forty specimens of each material were cured under Mylar strips and immersed in artificial saliva for 1 wk. Samples were tested with a profilometer to obtain baseline average surface roughness (Ra). Specimens of both RBCs were then finished and polished according to four techniques: (1) Sof-Lex disks; (2) Sof-Lex disks followed by Prisma Gloss; (3) Enhance points; (4) Enhance points followed by Prisma Gloss application. New readings of the roughness pattern were carried out and the difference of post-polishing and baseline values were analyzed. Results: ANOVA test (alpha= 0.05) did not show differences between materials (P= 0.9393) nor interaction effects (P= 0.3094), but significant difference among the finishing/polishing techniques were detected (P= 0.0157). Tukey's test showed that the smoothest surface was obtained when the specimens were treated by Sof-Lex followed by Prosma Gloss polishing paste; and the worst results were obtained after using Enhance points alone.